Innovation Of The Sipemang Application Using Qr Code For Monitoring And Preserving Mangrove Ecosystems In Pari City Village - Sri Wahyuni; Abdul Khaliq; Hanifah Mutia Zaida Ningrum Amrul; Aulia Akbar (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Mangrove ecosystems have an important role in maintaining the balance of the coastal environment. However, its existence is increasingly threatened by human activities and climate change. Effective monitoring and preservation of mangrove ecosystems is crucial. Kota Pari Village, with its mangrove potential, needs an innovative system to support these efforts. Therefore, this study aims to develop a QR Code-based Mangrove Monitoring Information System application "SIPEMANG". This application is designed to facilitate monitoring mangrove conditions, collecting data on mangrove species, and involving the community in mangrove conservation. Community involvement is not only the community around the village of Pari City but through the application can reach community involvement around the world. QR Codes placed on each mangrove tree allow quick access to specific information about the mangrove tree. The data collected through the application will be processed and analyzed to provide the latest information about the condition of the mangrove ecosystem in Kota Pari Village. So in addition to mangrove planters, the next important thing is to ensure that mangroves grow and develop properly. It is hoped that the SIPEMANG application can be an innovative solution in supporting the monitoring and preservation of mangrove ecosystems in a sustainable manner.